2019
DOI: 10.1016/j.bbagen.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Catechin-mediated restructuring of a bacterial toxin inhibits activity

Abstract: Background: Catechins, polyphenols derived from tea leaves, have been shown to have antibacterial properties, through direct killing of bacteria as well as through inhibition of bacterial toxin activity. In particular, certain catechins have been shown to have bactericidal effects on the oral bacterium, Aggregatibacter actinomycetemcomitans, as well as the ability to inhibit a key virulence factor of this organism, leukotoxin (LtxA). The mechanism of catechin-mediated inhibition of LtxA has not been shown. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 72 publications
0
29
0
1
Order By: Relevance
“…Each curve was normalized by dividing by the corresponding 1‐hr time point of each growth curve to facilitate comparison between the curves. For a negative control, the same concentrations of C, a nongalloylated catechin was used; nongalloylated catechins, such as C, have been shown to have limited antibacterial properties (Ikigai, Nakae, Hara, Nakae, Hara, & Shimamura, ), and we have previously shown that C has limited anti‐toxin activity, in contrast to the galloylated catechins (Chang et al, ). Figure a shows that micromolar concentrations of EGCg inhibit the growth of A. actinomycetemcomitans .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each curve was normalized by dividing by the corresponding 1‐hr time point of each growth curve to facilitate comparison between the curves. For a negative control, the same concentrations of C, a nongalloylated catechin was used; nongalloylated catechins, such as C, have been shown to have limited antibacterial properties (Ikigai, Nakae, Hara, Nakae, Hara, & Shimamura, ), and we have previously shown that C has limited anti‐toxin activity, in contrast to the galloylated catechins (Chang et al, ). Figure a shows that micromolar concentrations of EGCg inhibit the growth of A. actinomycetemcomitans .…”
Section: Resultsmentioning
confidence: 99%
“…Grape extract was shown to inhibit the activity of the cholera toxin (CT) produced by Vibrio cholerae (Reddy et al, ); when the authors investigated the inhibitory activity of the specific polyphenolic compounds comprising the extract, they observed that EGCg was the most active component (Cherubin et al, ). Similarly, we have shown that EGCg deactivates the toxic activity of the leukotoxin (LtxA) produced by A. actinomycetemcomitans by altering the secondary structure of LtxA and inhibiting the toxin's binding to cholesterol on the host cell membrane (Chang et al, ). Our finding closely reflects a previous study, in which it was shown that Psidium guajava (guava) extracts, particularly those from the leaves and twigs, neutralized the activity of LtxA by binding directly to the secreted LtxA rather than interacting with the host cell (Kwamin et al, ); guava leaves and bark have been reported to contain significant amounts of polyphenolic compounds, including catechins (Barbalho et al, ).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Catechins are polyphenols commonly found in foods like green tea, cocoa, red wine, along with a variety of fruits and vegetables, and are attributed to numerous health benefits due to their antioxidant and antimicrobial properties (Taylor, Hamilton‐Miller, & Stapleton, 2005; Yamagata, Tagami, & Yamori, 2015). Inspired by a report of inhibition of LtxA activity by catechins (Kawashima, 2011), as well as inhibition of A. actinomycetemcomitans OMVs (Saito, Tsuzukibashi, & Takada, 2012), we conducted a study to understand the mechanism of this inhibition (Chang, Huang, Lin, & Brown, 2019). This study investigated the inhibitory effects of six catechins.…”
Section: Anti‐ltxa Strategiesmentioning
confidence: 99%
“…Catechins are the most frequent and abundant polyphenolic compounds. The major green tea catechins include epigallocatechin-3-gallate (EGCG) and epicatechin −3-gallate (ECG), which constitute about 50 to 65% of total catechins and have a broad spectrum of antimicrobial activity against both of grampositive and gram-negative bacteria (Chang, Huang, Lin, & Brown, 2019).…”
Section: Introductionmentioning
confidence: 99%